Role of Optical Neuromonitoring in Neonatal Encephalopathy—Current State and Recent Advances - Harvey-Jones, Kelly; Lange, Frederic; Tachtsidis, Ilias; Robertson, Nicola J.; Mitra, Subhabrata (Frontiers in Pediatrics, 2021)
Neonatal encephalopathy (NE) in term and near-term infants, is a significant global health problem; the worldwide burden of disease remains high despite the introduction of therapeutic hypothermia. Assessment of injury severity and effective management in the neonatal intensive care unit (NICU) relies on multiple monitoring modalities, from systemic to brain-specific. Current neuromonitoring tools provide information utilised for seizure management, injury stratification and prognostication, whilst systemic monitoring ensures multi-organ dysfunction is recognised early and supported wherever needed. The neuromonitoring technologies currently used in NE however, have limitations in either their availability during the active treatment window or their reliability to prognosticate and stratify injury confidently in the early period following insult. There is therefore a real need for a neuromonitoring tool that provides cot-side, early and continuous monitoring of brain health which can reliably stratify injury severity, monitor response to current and emerging treatments and prognosticate outcome. The clinical use of near-infrared spectroscopy (NIRS) technology has increased in recent years. Research studies within this population have also increased, alongside the development of both instrumentation and signal processing techniques. Increasing use of commercially available cerebral oximeters in NICU, and the introduction of advanced optical measurements using broadband NIRS (BNIRS), frequency domain NIRS (FDNIRS) and diffuse correlation spectroscopy (DCS) have widened the scope by allowing the direct monitoring of oxygen metabolism and cerebral blood flow, both key to understanding pathophysiological changes and predicting outcome in NE. This review discusses the role of optical neuromonitoring in NE, and why this modality may provide the next significant piece of the puzzle towards understanding the real time state of the injured newborn brain.